Efficacy of a novel mixture of substances derived from food and food additives for controlling Dermanyssus gallinae (Mesostigmata: Dermanyssidae) - Odaka, Makiko; Matsuo, Kazunori; Ogino, Kazumasa; Kanazawa, Tamotsu; Baba, Ryoko; Sakata, Yoshiyuki; Asada, Kenichi; Kasa, Syoujirou; Takai, Kenji; Maeda, Ken (Applied entomology and zoology, 2019)
Dermanyssus gallinae De Geer (Mesostigmata: Dermanyssidae), also known as poultry red mite, causes serious economic losses to the poultry industry worldwide. In this study, a mixture of substances derived from food and food additives (SFF), including a polysaccharide extract from laver seaweed, Pyropia yezoensis (Bangiaceae), was examined for acaricidal effects. Treatment with SFF was more effective in killing mites by blocking their respiratory organs than SFF without the polysaccharide extract. In a field trial, treatment with SFF reduced the density of mites in a poultry farm as well as the proportion of blood-stained eggs. This SFF appears useful for controlling the population of D. gallinae in the poultry farms.